Promoter Variants of the ADAM10 Gene and Their Roles in Temporal Lobe Epilepsy - Tao, Hua; Zhao, Jianghao; Zhou, Xu; Ma, Zhonghua; Chen, Ying; Sun, Fuhai; Cui, Lili; Zhou, Haihong; Cai, Yujie; Chen, Yanyan; Zhao, Shu; Yao, Lifen; et al. (Frontiers in Neurology, 2016)
Previous evidence has indicated that down-regulated ADAM10 gives rise to epileptic seizures in Alzheimer’s disease, and this study investigated the association of ADAM10 with temporal lobe epilepsy (TLE) from a genetic perspective. A total of 496 TLE patients and 528 healthy individuals were enrolled and genotyped for ADAM10 promoter variants (rs653765 G>A and rs514049 A>C). The alleles, genotypes, and haplotypes were then compared to clarify the association of these variants with TLE, and their impacts upon age at onset, initial seizure types before treatments, and responses to drug treatments. In cohorts I, II, and I+II, the frequencies of the A allele and AA genotype at rs514049 were consistently increased in the cases compared to the controls (p=0.020 and p=0.009; p=0.008 and p=0.009; p=0.000 and p=0.000, q=0.003 and q=0.002, respectively). In contrast, the frequency of the AC haplotype (rs653765-rs514049) decreased in cohorts I+II (p=0.013). Further analyses of the TLE patients indicated that the AA genotype functioned as a predisposing factor to drug-resistant TLE and the AC haplotype as a protective factor against generalized tonic clonic seizures (GTCS) and drug-resistant TLE. This study is the first to demonstrate an association of the ADAM10 promoter variants with TLE. In particular, the AA genotype and AC haplotype showed their effects upon GTCS and drug-resistant TLE.